Effect of van der Waals force on bubble dynamics in bubbling fluidized beds of ellipsoidal particles. (2nd February 2020) - Shrestha, S.; Kuang, S.B.; Yu, A.B.; Zhou, Z.Y.
Highlights: The combined effect of van der Waals force and particle shape are studied by CFD-DEM. Cohesive force delays the time of bubble formation. Bubble cloud thickness is larger for ellipsoids compared to spheres. Bubble size and velocity decreases with the increase of van der Waals force. Ellipsoids have different flow patterns under the influence of cohesive force. Abstract: This paper presents a numerical analysis of the combined effect of cohesive van der Waals force and particle shape on bubble dynamics in gas fluidization. The van der Waals force is incorporated into the CFD-DEM model and the magnitude varies from 0 to 20 times Hamaker constant ( Ha = 2.1 × 10 −21 J), representing non-cohesive to highly cohesive particles. Particles with aspect ratios at 0.5 (oblate), 1 (spherical) and 2 (prolate) are employed to represent disc-like, spherical and rod-like particles, respectively. The results show that under the influence of cohesive force, features such as bubble splitting and coalescence are affected significantly by aspect ratios of ellipsoidal particles. With the increase of Hamaker constant, bubble size and rising velocity decrease, and the bubble shape becomes irregular and vertically oblong. Moreover, the increase of van der Waals force leads to the transformation to non-bubbling fluidization for ellipsoids, but channelling occurs for spheres.